VALORIZATION OF RESIDUES WASTE FROM PINEAPPLE FOR CRUDE BROMELAIN ENZYME POWDER PRODUCTION - Kanjanarong, Jarupat; Suhem, Kitiya; Plongbunjong, Vijitra (Srinakharinwirot University Journal of Sciences and Technology, 2024)
The objective of this research was to investigate the extraction of crude bromelain enzyme from pineapple residues waste (Ananas comosus), including the bromelain enzyme powder production. The results showed that the residues waste had the potential for crude bromelain enzyme production. However, the stem exhibited the highest activity and specific enzyme activity, with values of 182.5 ± 1.0 Units/ml and 16.9 ± 0.5 Units/mg, respectively, which were significantly (p≤0.05) higher than those of the peel, core, and crown. In addition, the thermal stability of the bromelain enzyme (25-65°C) was studied. It was found that the crude bromelain enzyme had thermal stability at 35°C, but its stability decreased at temperatures above 45°C, with no specific enzyme activity observed at 65°C. Furthermore, the crude bromelain extracted from the stem, which exhibited the highest specific enzyme activity, was processed into powder using freeze-drying technology. The results indicating that the storage of bromelain enzyme powder at 4°C gave higher specific enzyme activity than storage at 35°C for a period of 28 days. Therefore, residual waste materials from pineapples have the potential to be utilized in enzyme production and can be further developed into high-value substances or products.